PENGUKURAN KINERJA ORGANISASI BPSPAMS MENGGUNAKAN INDIKATOR MALCLOM BALDRIGE CRITERIA FOR PERFORMANCE EXCELLENCE (MBCFPE) PADA PROGRAM PAMSIMAS DI DESA PURWOSARI, WONOBOYO, TEMANGGUNG - Dhita Arika; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
The availability of clean water is a basic need of the community. This is realized by the government through the community based Drinking Water and Sanitation Provision Program (PAMSIMAS). Previous studies on PAMSIMAS mostly focused on program evaluation, community participation, and the effectiveness of the program. Research on the performance of organizations that depart from the community as program administrators is still rarely found. Therefore, this research examined the performance of the Managing Board of Drinking Water and Sanitation (BPSPAMS) which manages the built drinking water facilities, and which has a great influence on the sustainability of program operations. The purpose of this study was to assess the performance of the BPSPAMS in the PAMSIMAS Program in Purwosari Village, Wonoboyo, Temanggung, using the 7 indicators of Malclom Baldrige for Performance Excellence (Leadership, Strategic Planning, Community Focus, Information and Knowledge Management System, Team Focus, Operational Focus, and Work Results). The population taken in this study were members of the BPSPAMS in Purwosari village. This research used descriptive quantitative method, using the determination of the interval class and calculate the weight of each indicator. The results showed that the BPSPAMS has well performed since the provided are in accordance with the community needs, a good development Plan exist, members' knowledge is in accordance with the conditions of the field, and community relations with members are in accordance with ethical values and politeness. However, some internal problems are found, such as the inactive leaders and some members in carrying out their duties and functions, as well as lack of organizational revenue that hinders the fulfillment of the operational needs. It is recommended that all members of BPSPAMS in Purwosari village to reorganize, and collaborate with those who can help with financial needs, and not to use Malclom Baldrige for Performance Excellence indicators in the scope of performance measurement for public organization, especially in rural level organizations.